Rehabilitation of an Extremely Resorbed Edentulous Mandible by Short and Narrow Dental Implants - Ines Kovacic; Sanja Persic; Josip Kranjcic; Nikolina Lesic; Asja Celebic (Hindawi Limited, 2018)
Serious consequences of long-term complete denture wearing may be extreme residual ridge atrophy and a reduced area of keratinized oral mucosa of a denture-bearing area. This paper presents five clinical cases of extreme mandibular ridge atrophy, rehabilitated by means of mandibular overdentures retained by short mini dental implants. The patients had a reduced mandibular bone volume in the interforaminal region, bone height less than 10 mm, and buccolingual bone width less than 4 mm. In order to avoid bone augmentation, patients received four short mini dental implants (MDIs) (6 or 8 mm long; 2.0 or 2.5 mm wide) for the support of mandibular overdentures, which is a new rehabilitation option. After insertion, the MDIs were early loaded with new mandibular overdentures reinforced with the CoCr framework. The patients have been wearing their overdentures for 2 years. One MDI broke during insertion and a new one was added. One patient lost one MDI but successfully continued to wear the overdenture retained by the remaining three MDIs. Mean marginal bone loss (MBL) was 0.20 ± 0.19 mm. Patients significantly improved their OHRQoL and chewing function by reducing the summary scores of the OHIP-14 and the chewing function questionnaires. The improvements remained unchanged throughout the observation period.